A study on the feasibility and mechanism of enhanced co-coagulation dissolved air flotation with chitosan-modified microbubbles. (April 2021) - Wang, Yonglei; Sun, Wentao; Ding, Luming; Liu, Wei; Tian, Liping; Zhao, Yinhe; Zhang, Mengyu; Wang, Xuelin
Graphical abstract: Schematic diagram of the adhesion mechanism of Posi-CCDAF. The results show that the enhancement in the removal of particles in water by the Posi-CCDAF process is significant. The pH value of the dissolved-air reflux water and the dosage ratio of chitosan have a direct impact on the removal efficiency of CCDAF. The results also suggested that the removal effect of the process on humic and fulvic acids with high molecular weights and hydrophobicity was significantly improved. However, because hydrophobic organics are more likely to produce TCM during reaction with chlorine, the removal effect of TCM in THMFP was the most significant. The addition of chitosan makes the formed flocs denser, and the microbubbles participate in the copolymerization process, causing them to be firmly wrapped in flocs, finally enhancing the decontamination efficiency of CCDAF. The results could be used to improve the CCDAF performance and effluent quality and provide a new method to enhance the adhesion of flocs in the process of drinking water treatment by air flotation. Abstract: Water from the Yellow River reservoir is treated by dissolved air flotation (DAF), but the flocs formed are loose and easily desorbed. To solve this problem, a new air flotation process, i.e., Posi-co-coagulation dissolved air flotation (Posi-CCDAF), was developed by combining DAF with microbubble surface modification technology. The feasibility of the Posi-CCDAF process was verified by using chitosan to modify the surfaces of the microbubbles. The optimal dosage ratio of chitosan/coagulant was 0.4, and the optimal pH of the reflux water was 6.00. The removal characteristics of organic pollutants under the optimal conditions were studied. The removal characteristics of natural organic matter (NOM) with different molecular weights before and after adding chitosan were compared, and the removal efficiency of disinfection byproduct precursors was evaluated. Microscopic analysis was used to observe the bubble floc adhesion process and flocs during the copolymerization process before and after the addition of chitosan. The results showed that chitosan promoted the removal of hydrophobic macromolecular organics and the trihalomethane formation potential (THMFP) by CCDAF. On the one hand, the surface of modified microbubbles in Posi-CCDAF was positively charged, which provided electrostatic force to enhance the adhesion of flocs during polymerization; on the other hand, the combination of chitosan and macromolecular organics in water formed a capture network, which made the bubble flocs larger and caused them to adhere tightly, improving the removal effect of air flotation.